2009
DOI: 10.4028/www.scientific.net/msf.615-617.719
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bipolar Gate-to-Drain Current on the Electrical Properties of Vertical Junction Field Effect Transistors

Abstract: Electron-hole recombination-induced stacking faults have been shown to degrade the I-V characteristics of SiC power p-n diodes and DMOSFETs with thick drift epitaxial layers. In this paper, we investigate the effect of bipolar gate-to-drain current on vertical-channel JFETs. The devices have n- drift epitaxial layers of 12-μm and 100-μm thicknesses, and were stressed at a fixed gate-to-drain current density of 100 A/cm2 for 500 hrs and 5 hrs, respectively. Significant gate-to-drain and on-state conduction curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Under bipolar gate-to-drain current flow, electron -hole pair recombination at basal-plane-dislocations (BPDs) in the drift layer of the VJFET induces stacking fault formation and expansion [42,43], which causes significant degradation in the electrical characteristics of SiC power p -n diodes and DMOSFETs with thick drift epitaxial layers [5,44]. To assess the reliability of cascode-switch power conditioning with no external diodes present, the effect of bipolar gate-to-drain current on the electrical characteristics of 1200 V vertical-channel JFETs with 12 μm drift epitaxial layers was investigated [45]. The VJFETs were grown on substrates in which the density of BPDs was not suppressed during epitaxial growth.…”
Section: Reliability Of the 1200 V Normally-off All-sic Vjfet Cascodementioning
confidence: 99%
See 1 more Smart Citation
“…Under bipolar gate-to-drain current flow, electron -hole pair recombination at basal-plane-dislocations (BPDs) in the drift layer of the VJFET induces stacking fault formation and expansion [42,43], which causes significant degradation in the electrical characteristics of SiC power p -n diodes and DMOSFETs with thick drift epitaxial layers [5,44]. To assess the reliability of cascode-switch power conditioning with no external diodes present, the effect of bipolar gate-to-drain current on the electrical characteristics of 1200 V vertical-channel JFETs with 12 μm drift epitaxial layers was investigated [45]. The VJFETs were grown on substrates in which the density of BPDs was not suppressed during epitaxial growth.…”
Section: Reliability Of the 1200 V Normally-off All-sic Vjfet Cascodementioning
confidence: 99%
“…No further on-state drain current degradation was observed after an additional 495 hours of gate-to-drain stressing. In addition, performing multiple 350 °C annealing cycles (identical to those that recovered degradations in 100 μm drift layer VJFETs [45]) had no measurable impact on the post-stress on-state drain current characteristics. Thus, the observed post-stress, on-state drain-current degradation is attributed to a "burn-in" effect.…”
Section: Figure 18mentioning
confidence: 99%
“…There has been some recent success at limiting BPD densities during epitaxial growth by leveraging the aforementioned BPD 'turning' phenomenon, [10][11][12][13] however, their density still remains appreciable and therefore over time, SF-induced device degradation still occurs. Furthermore, it has also been reported that this degradation is not limited strictly to bipolar devices, but also adversely affects unipolar devices such as DMOSFETs, 14,15 VJFETs, 16 and MPS diodes 14 where bipolar injection into the active area of the device is possible.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the minority carrier recombination in bipolar operation reduces switching speeds, which increases switching losses. Finally, bipolar recombination at basal-plane dislocations in the thick drift layers of ∼10-kV VJFETs induces stacking fault formation and expansion, which can cause forward-voltage degradation [15]. Therefore, high-current-gain operation at a low unipolar (gate biased below its built-in potential) ON-state resistance is required for efficient and reliable VJFET power switching.…”
mentioning
confidence: 99%